Vivo [videorecording (DVD)] - DeMicco, Kirk; Hudes, Quiara Alegría; Barsocchini, Peter, 1952- (Sony Pictures Home Entertainment, 2022)
Vivo, a one-of-a-kind kinkajou, spends his days playing music with his beloved owner Andrés. But when tragedy strikes, it's up to Vivo to deliver a message that Andreš never could: a love letter to his old partner, the famous Marta Sandoval, in the form of a song. Yet in order to get to Marta, who lives a world apart, Vivo will need the help of Gabi, an energetic tween who bounces to the beat of her own offbeat drum, to fulfill his owner's wishes.